P-557 Fresh Transfer with Supernumerary PGT-A Biopsy: The Best of Both Worlds. (30th June 2022) - Jiang, V; Dimitriadis, I; Souter, I; Bormann, C.L
Abstract: Study question: What is difference in time to pregnancy for patients between 35-40 years who undergo fresh versus frozen-thawed embryo transfers with or without PGT-A? Summary answer: Patients undergoing fresh embryo transfer (ET) had a shorter time to pregnancy within the same cycle compared to patients electing for freeze-all cycles. What is known already: When comparing clinical pregnancy rates following fresh versus frozen-thawed embryo transfers, multiple studies have shown a higher clinical pregnancy rate among frozen-thawed embryo transfers compared to fresh embryo transfers. Particularly for patients over 35 years, there has been a growing national trend towards elective freeze-all cycles, for reasons such as to pursue preimplantation genetic testing for aneuploidy (PGT-A). While PGT-A testing can be effective in reducing miscarriage in patients age 38-40, there is limited studies evaluating time to pregnancy within this population, especially in the context of each passing month's effect on fertility. Study design, size, duration: Retrospective review was performed for 697 IVF cycles and 881 transfers from January 2016 – December 2021 at a single academic fertility center in Boston, Massachusetts. Two-tailed t-tests and analysis of variance (ANOVA) were used to compare differences, with p-value less than 0.05 set for statistical significance. All PGT-A testing as performed using a modified FAST-SeqS next generation sequencing method (Invitae, San Francisco, CA). Participants/materials, setting, methods: Cycle characteristic of patients between 35-40 were categorized to four groups: Fresh ET with PGT-A of supernumerary embryos (82 transfers), Fresh ET without PGT-A (526 transfers), Freeze-all cycle with PGT-A (223 transfers), and Freeze-all cycle without PGT-A (50 transfers). All averages were calculated within one IVF cycle with a single cohort of embryos. Time to pregnancy was calculated in days from day of retrieval to positive serum beta-human chorionic gonadotropin (bHCG). Main results and the role of chance: Among the 881 transfers, 478 had fresh ETs and 403 had frozen-thawed ETs with or without PGT-A respectively. When comparing fresh and freeze-all cycles, there was no difference in average numbers of transfers performed to achieve a clinical pregnancy (1.27 fresh vs 1.25 freeze-all, p = 0.56). For patients who didn't elect for PGT-A, there was no difference in number of embryos transferred (1.86 for fresh versus 2.06 for freeze-all, p = 0.54). For patients who elected for PGT-A, the average number of embryos transferred was higher for patients that opted for fresh transfer over freeze-all (1.67 for fresh ET with PGT-A of supernumerary embryos versus 1.24 for freeze-all PGT-A, p = 0.0025). Average days from oocyte retrieval to pregnancy was significantly lower for all fresh ETs (28.8 days for fresh ET without biopsy, 26.6 days for fresh ET with biopsy of supernumerary embryos, p < 0.0001) compared to all freeze-all transfers (110.9 days for freeze-all ET without biopsy, 119.5 days for freeze-all ET with biopsy, p < 0.0001). This delay in time to pregnancy is partially attributed to pending genetic testing results, however, these results usually return in 2-3 weeks, which does not account for the near 3-month delay in time to pregnancy among freeze-all cycles. Limitations, reasons for caution: These retrospective findings were of all women who achieved pregnancy from one retrieval. These results are not reflective of the patients who needed to undergo multiple cycles to achieve pregnancy, or patients who never achieved pregnancy. Wider implications of the findings: These findings suggest that PGT-A may be offered to patients > 35 to minimize the number of embryos for transfer. Patients opting for a fresh transfer of an untested embryo and biopsy of supernumerary embryos had a nearly 3-month shorter time to pregnancy than those electing for a freeze-all cycle Trial registration number: not applicable